PENGARUH PEMBERIAN KULIT PISANG SEBAGAI PENGGANTI KONSENTRAT KOMERSIL TERHADAP GAMBARAN HEMATOKRIT, HEMOGLOBIN DAN OVARIUM DOMBA - , TRIAWAN ALKAUSAR, drh. Yuda Heru Fibrianto, M.P., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Banana peel is a potential waste to be utilized as a farm animal food. Banana peel contains high crude fiber and high protein. Banana peel contains 13.0 % crude fiber, 7.7 % protein, and 1.6 mg/100g iron. Crude fiber, protein and iron are the important nutrients for growth and health of sheep. The purpose of this research is to analyze the effect of feeding banana peel on the profile of hematocrit, hemoglobin and ovarium size of sheep, so that banana peel can be the alternative commercial concentrate with cheaper price than the recent commercial concentrate . This research was held for 4 weeks at a sheep barn of Mr. Sadiyan at RT 01 / RW 21, Sumbersari, Moyudan, Sleman. This research used 12 sheeps divided into 4 groups of treatment. Control group (K) being fed with forage and the mixture of polar brand and bran every other day, tratment 1 group (P1) being fed with forage and the mixture of 90% bran and 10% banana peel flour every other day, treatment 2 group (P2) being fed with forage and the mixture of 70% bran and 30% banana peel flour every other day and tratment 3 group (P3) being fed with forage and the mixture of 50% bran and 50% banana peel flour every other day. At the first and fourth week each groups of treatment had their blood drawn. The paramaters that would be observed were hemoglobin concentration and hematocrit. The method of data analysis used analysis of variance (ANOVA). Ovarium size measurement was done at the fourth week used ultrasonography (USG). The result of the research showed that feeding banana peel did not give the significant effect to hematocrit, hemoglobin and ovarium of sheep. It has been proven that feeding banana peel was able to substituted bran concentrate as an alternative concentrate according to hemoglobin, hematocrit profile and ovarium size. Key words : sheep, banana peel, hemoglobin, hematocrit, ovarium.